2005
DOI: 10.1029/2004ja010608
|View full text |Cite
|
Sign up to set email alerts
|

Statistical studies of auroral MF burst emissions observed at South Pole Station and at multiple sites in northern Canada

Abstract: [1] Auroral MF burst is a broadband impulsive natural radio emission of auroral origin observed at ground level in the frequency range 0.8-4.5 MHz. Application of a semiautomated analysis method to data collected at South Pole Station, 74°magnetic latitude, results in a database of frequencies, amplitudes, and universal times of MF burst emissions observed during 1 January-31 December 2003. Besides confirming that MF burst emissions are observed at ground level only during darkness and that magnetic local time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…The resulting frequencies would range from the plasma or upper hybrid frequency at the F peak, of order foF2, to the plasma frequency at an altitude where collisions prevent the effective excitation of the waves, or the frequency corresponding to the peak plasma frequency in a blanketing E layer if one exists. This mechanism fits properties of MF burst known from previous observations, including: the frequency range of 1.3–4.5 MHz, which is similar to the typical range of plasma and upper hybrid frequencies in the F layer; the polarization of the emissions which is consistent with LO mode; the association with auroral activity and substorm onsets, when auroral electron beams penetrate the ionosphere and excite Langmuir and upper hybrid waves there; and extension of MF burst emissions to higher frequencies when conditions favor higher densities, such as early and late winter conditions at South Pole [ LaBelle et al , 2005] or times when ISR records increases in density [ LaBelle et al , 1997]. Open questions are whether the electron beams persist to sufficiently low altitudes with sufficient free energy to excite Langmuir or upper hybrid waves on the F‐region bottomside, and whether the beam can persist to excite waves over a sufficiently broad altitude range to explain the broadband nature of the MF burst.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The resulting frequencies would range from the plasma or upper hybrid frequency at the F peak, of order foF2, to the plasma frequency at an altitude where collisions prevent the effective excitation of the waves, or the frequency corresponding to the peak plasma frequency in a blanketing E layer if one exists. This mechanism fits properties of MF burst known from previous observations, including: the frequency range of 1.3–4.5 MHz, which is similar to the typical range of plasma and upper hybrid frequencies in the F layer; the polarization of the emissions which is consistent with LO mode; the association with auroral activity and substorm onsets, when auroral electron beams penetrate the ionosphere and excite Langmuir and upper hybrid waves there; and extension of MF burst emissions to higher frequencies when conditions favor higher densities, such as early and late winter conditions at South Pole [ LaBelle et al , 2005] or times when ISR records increases in density [ LaBelle et al , 1997]. Open questions are whether the electron beams persist to sufficiently low altitudes with sufficient free energy to excite Langmuir or upper hybrid waves on the F‐region bottomside, and whether the beam can persist to excite waves over a sufficiently broad altitude range to explain the broadband nature of the MF burst.…”
Section: Discussionmentioning
confidence: 75%
“… Shepherd et al [1997] show that MF bursts are left‐hand polarized. LaBelle et al [1997] also presented waveform measurements, though restricted to a 10‐kHz bandwidth, which suggested sub‐structure with timescales as short as 100–300 μ s. LaBelle et al [2005] reported statistical and case studies of MF burst events at South Pole Station and several sites in northern Canada, in which they confirmed MF burst to be observed at ground level only during darkness, and that their occurrence rate is controlled heavily by local magnetic time, maximized during premidnight hours; a case study of an event observed at five different Canadian observatories shows that the MF burst intensity shifts poleward during the course of the event.…”
Section: Introductionmentioning
confidence: 95%
“…[10] The 4f ce roar did not accompany any other types of MF/HF auroral radio emissions (2f ce roar, 3f ce roar and MF burst), which are detected only during local darkness and are most common in the premidnight hours [e.g., Weatherwax et al, 1995;LaBelle et al, 1997;LaBelle and Weatherwax, 2002;LaBelle et al, 2005]. This difference is causallyrelated to dependence of ionospheric radio wave absorption on frequency: during daylight hours, photoionization enhances electron densities in the ionospheric D-and E-regions to increase radio wave absorption, which is severer for lower frequency waves.…”
Section: Discussionmentioning
confidence: 99%
“…MF burst shows a broadband impulsive feature with a bandwidth of 1-2 MHz in a frequency range of 0.8-4.5 MHz (LaBelle et al, 2005). The polarization character of 2 f ce roar and MF burst have been identified as left-handed polarized waves by Shepherd et al (1997), implying that they should propagate in the L-O mode in the ionosphere.…”
Section: Introductionmentioning
confidence: 99%